Current Practices and Pitfalls of ELT Syllabi for Developing Engineering Students' Communicative English in Bangladesh - Islam Khan, Mohammad Ehsanul; Seraj Bhuiyan, Mohammad Shahazahan; Islam Khan, Mohammad Ekramul (Mextesol journal, 2024)
The current practices and shortcomings of engineering students' English language teaching (ELT) syllabi were examined from the perspectives of learners and teachers in English as a foreign language (EFL) context. The syllabi included content that had little impact on students' communicative competence in English (CC-E). Students were generally concerned about their professional communication abilities. In this study, the researchers collected data from ten engineering-focused universities in Bangladesh. These universities' existing ELT syllabi (ELT-S) were examined, seeking the current practices and pitfalls. The study sampled 152 participants from the selected universities. The study followed a mixed-method approach. In the qualitative technique, content analysis, focus group discussion (FGD), and interviews were employed for data collection, while survey questions were used in the quantitative approach. The study's findings revealed that the existing English syllabi of those selected universities required updating and modification to meet the identified professional requirements regarding the type, credit allotment, content, classroom practices, class size, policies, etc. The improvements included redesigning English syllabi, material, and teaching methods to improve engineering students' communicative abilities. A uniform curriculum with at least one English language sessional course per semester in all engineering majors was strongly recommended.